Comprehensive Modular Synthesis of Ganglioside Glycans and Evaluation of their Binding Affinities to Siglec‐7 and Siglec‐9 - Avijit K. Adak; Hsin‐Kai Tseng; Shu‐Yen Chang; Yu‐Ching Chiang; Ke‐Hong Lyu; Yun‐Sheng Lee; Wen Lu; Wen‐Hua Kuo; Takashi Angata; Chun‐Cheng Lin (Advanced Science)
Abstract In the present work, bacterial glycosyltransferases are utilized to construct ganglioside glycans in a convergent approach via a sugar‒nucleotide regeneration system and one‐pot multienzyme reactions. Starting from β‐lactoside enables the diversification of both the glycan moieties and the linkages in the lower α‐arm and upper β‐arm. Overall, a comprehensive panel of 24 natural a‐series (GM3, GM2, GM1a, GD1a, GT1a, and fucosyl‐GM1), b‐series (GD3, GD2, GD1b, GT1b, and GQ1b), c‐series (GT3, GT2, GT1c, GQ1c, and GP1c), α‐series (GM1α, GD1aα, and GT1aα), and o‐series (GA2, GA1, GM1b, GalNAc‐GM1b, and GD1c) ganglioside glycans are prepared, which are suitable for biological studies and further applications. Moreover, a microarray is constructed with these synthesized ganglioside glycans to investigate their binding specificity with recombinant Fc‐fused Siglec‐7 and Siglec‐9, which are immune checkpoint‐like glycan recognition proteins on natural killer cells. The microarray binding results reveal that GD3 and GT1aα are specific ligands for Siglec‐7 and Siglec‐9, respectively, and this discovery can lead to the identification of appropriate ligands for investigating the roles of these Siglecs in immunomodulation.